Imigrantes haitianos no mercado de trabalho formal brasileiro - Cardoso, Felipe Pureza (2021)
In 2010, an earthquake hit Haiti and caused thousands of citizens from that country to migrate to Brazil. Therefore, this dissertation aims to analyze how the insertion of Haitian immigrants in the Brazilian labor market takes place, assuming that they are occupied in the segments in which they have greater comparative advantages in relation to the Brazilians nationals. Thus, we estimate typically Mincerian equations through quantile regressions in addition to an Oaxaca-Blinder decomposition in a sample with Haitians, Brazilians in the same occupations and natives in other jobs from the 2019 Annual List of Social Information (RAIS). It is verified that the average salary of those who are working in occupations considered to be Haitian is lower, which may be an indication of the inferior quality and precariousness of these jobs. Furthermore, evidence is found that the wage determinants act differently for each group, valuing Brazilian workers more. In this context, Haitians act as complements to Brazilians who are in different occupations and as substitutes for those who work in the same positions, but only in the lower income brackets.